The McGraw-Hill Reader: Issues Across the Disciplines - Muller Gilbert H (Mc Graw Hill Higher Education, 2007)
The McGraw-Hill Reader addresses the liberal arts tradition, cross-curricular ideas, and diverse viewpoints through more than one hundred quality prose works from prominent writers and thinkers. A range of readings from both classic and contemporary sources and from across the disciplines—from education, the social sciences, business and economics, the humanities, and the sciences—provoke critical thought and effective writing.